Topological Charge Measurement of the Mid-Infrared Vortex Beam via Spatially Dependent Four-Wave Mixing in an Asymmetric Semiconductor Double Quantum Well - Song, Yi; Li, Ling; Shui, Tao; Hu, Die; Yang, Wen-Xing (Frontiers in Physics, 2022)
We theoretically propose a scheme to measure the topological charge (TC) of a Mid-infrared vortex beam via observing the intensity distribution of the four-wave mixing (FWM) field in an asymmetric semiconductor double quantum-well. Due to the existence of Fano-type interference, the special inherent interference takes place and thus generates the interference-type phase and intensity patterns for the FWM field. Furthermore, it is demonstrated that the intensity and visibility of the interference-type intensity pattern can be drastically manipulated by adjusting the intensity and detuning of the control field. Subsequently, we perform the TC measurement of the vortex driving field via directly monitoring the number of light spots of the FWM field. By choosing the suitable control parameters, the detectable value of the TC can reach to 120 with the visibility exceeding 0.97. Our scheme may provide the possibility for the realization of Mid-infrared OAM detector in a compact solid-state system.